Pelaksanaan Pemberian Aroma Terapi Lavender terhadap Mual Muntah pada Ibu Hamil Trimester Pertama di PMB Ronni Siregar Deli Serdang - Elisa Silvia Aritonang; Ronni Naudur Siregar; Nurcahaya Nainggolan; Dewi Carolina Panjaitan (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Nausea and vomiting are common discomforts experienced by 50% of pregnant women in the first trimester. One of the implementations to reduce nausea and vomiting with non-pharmacological therapy is the provision of lavender aromatherapy. The purpose of this study was to determine whether there was an effect of giving Lavender aromatherapy on nausea and vomiting in pregnant women in the first trimester at PMB Ronni Siregar Deli Serdang. The research method used was Quasi-experimental using nonequivalent control group design. The sampling technique used in this study was Total sampling based on Inclusion and Exclusion criteria, the number of samples was 30 respondents (15 intervention groups and 15 control groups). The results showed that the average value of respondents in the intervention group in the nausea and vomiting value before giving lavender aromatherapy was Mean 13.5 standard deviation 3,521. in the intervention group after being given treatment, a mean value of 10.6 was obtained with a standard division of 4,459. Based on the t-test, a p-value of 0.000 was obtained, which means it is smaller than the significant value <0.05. The conclusion of this study is that there is an Effect of Lavender Aromatherapy on Nausea and Vomiting in Pregnant Women in the First Trimester at PMB Ronni Siregar Deli Serdang. This study expects Midwives to provide health promotion and education, namely by improving their midwifery care, especially for Pregnant Women with nausea and vomiting during pregnancy, in addition to explaining the non-pharmacological benefits in reducing nausea and vomiting during pregnancy.